Pola pembinaan karakter disiplin siswa berbasis nilai-nilai islam di smk izzul islam salem - Widia Triaprianti; Haris Diar Rizki; Desi Sapitri; Nita Medyiana (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the pattern of character development of student discipline based on Islamic values ​​at SMK Izzul Islam Salem. The study used a qualitative approach with a case study research type. Data were obtained through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, homeroom teachers, and students. Data analysis was conducted using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions through triangulation techniques. The results of the study indicate that the development of student discipline character is carried out through five main patterns, namely exemplary behavior (uswah hasanah), habituation (habituation), supervision and control, the provision of educational sanctions, and internalization of Islamic values. The internalized Islamic values ​​include obedience (ta'ah), responsibility (amanah), honesty (shiddiq), and consistency (istiqamah). Supporting factors for character development of discipline include a religious school environment, teacher role models, structured school programs, and support from the principal. Inhibiting factors include low awareness of some students, the influence of the social environment, and less than optimal family support. This study shows that the integration of Islamic values ​​in school culture contributes positively to the formation of students' disciplined character.